A LEAN PERSPECTIVE ON POST-DISASTER HOUSING RECONSTRUCTION IMPLEMENTATION IN CIANJUR - Dyla Midya Octavia; Taufika Ophiyandri; Akhmad Suraji; Benny Hidayat (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Post-disaster housing reconstruction is a critical recovery process that requires not only physical rebuilding but also effective coordination, administrative readiness, technical assistance, and community participation. However, reconstruction programmes often face delays, rework, quality problems, and low beneficiary satisfaction. This study aims to analyse the implementation of post-disaster housing reconstruction after the 2022 Cianjur earthquake from a Lean Construction perspective. A qualitative case study was conducted using institutional document analysis, semi-structured interviews, and field observations. The study involved 24 informants: 10 key informants from the central government, local government, technical actors, and local community leaders, and 14 beneficiary community members. The data were analysed through document review, thematic analysis, process analysis, and interpretation based on Lean Construction principles, including value, waste minimisation, flow, stakeholder coordination, and continuous improvement. The findings show that the reconstruction process in Cianjur was implemented through reimbursement, independent community-based reconstruction, and third-party implementation schemes. Four main implementation problems were identified: beneficiary data inconsistency, administrative complexity, limited technical knowledge and resources, and weak control of third-party implementation. From a lean perspective, these problems represent defects in information flow, overprocessing, resource bottlenecks, value leakage, and process interruptions that reduce value for beneficiaries. The study suggests that future post-disaster housing reconstruction should strengthen beneficiary data management, simplify administrative procedures, balance facilitator workloads, provide early technical education, and improve third-party monitoring to support more efficient, beneficiary-oriented reconstruction.